Upaya Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Al-Qur’an Hadist dengan Menggunakan Strategi Peer Lessons - Hidayat, Dace Arief; Arifah, Chusna; Rizal, Soni Samsu (Jurnal Penelitian Pendidikan Islam, 2016)
On the basis of the problems found in Madrasah Aliyah Terpadu Pakunagara known that the use of lecture, question, and answer could not optimize student learning outcomes in the subject of Quran Hadith. Therefore, researcher has tried to apply lessons peer strategy. The purpose of using this strategy is to maximize student learning outcomes in the subjects of Qur'an Hadith. The results show that this strategy can improve student learning outcomes in the subjects of Qur'an Hadith.